Bufadienolides originated from toad source and their anti-inflammatory activity - Zou, Denglang; Wang, Qiqi; Chen, Tao; Sang, Duocheng; Yang, Tingqin; Wang, Yuhan; Gao, Mengze; He, Fangfang; Li, Yulin; He, Liangliang; Longzhu, Duojie (Frontiers in Pharmacology, 2022)
Bufadienolide, an essential member of the C-24 steroid family, is characterized by an α-pyrone positioned at C-17. As the predominantly active constituent in traditional Chinese medicine of Chansu, bufadienolide has been prescribed in the treatment of numerous ailments. It is a specifically potent inhibitor of Na+/K+ ATPase with excellent anti-inflammatory activity. However, the severe side effects triggered by unbiased inhibition of the whole-body cells distributed α1-subtype of Na+/K+ ATPase, restrict its future applicability. Thus, researchers have paved the road for the structural alteration of desirable bufadienolide derivatives with minimal adverse effects via biotransformation. In this review, we give priority to the present evidence for structural diversity, MS fragmentation principles, anti-inflammatory efficacy, and structure modification of bufadienolides derived from toads to offer a scientific foundation for future in-depth investigations and views.